Microwave-assisted extraction and computational modelling of curcumin from turmeric (Curcuma longa) for sunscreen applications - Salmahaminati, Salmahaminati; Muchtar, Khopipah; Fajarwati, Febi Indah; Herawati, Mutiara; Kesumawati, Ayundyah (Jurnal Ilmiah Pertanian, 2025)
Excessive exposure to ultraviolet (UV) radiation from sunlight can cause skin damage, including premature aging, sunburn, and increased risk of skin cancer. While synthetic sunscreen agents are widely used, concerns over their long-term safety have driven interest in natural alternatives. In this study, curcumin was extracted from turmeric rhizomes (Curcuma longa) using microwave-assisted extraction (MAE) as a potential natural sunscreen. The highest yield was obtained using ethanol as solvent (5.5%), 100 watts of microwave power (5.7%), and solvent temperature of 50 °C (7.8%). Curcumin presence was confirmed by thin layer chromatography (TLC), with Rf values from 0.63 (methanol) to 0.82 (ethanol). Fourier transform infrared (FTIR) spectroscopy showed functional groups including O–H, C–H, C=C, C=O, and C–O, along with trans-C–H benzoate vibrations. ¹H-NMR spectra supported its presence, with chemical shifts at 3.80–3.92, 6.54–7.18, and 7.31–7.49 ppm. UV-Vis analysis revealed strong absorption in the UV-A region (320–420 nm), and DFT-based computational modelling showed peaks at 276 and 405 nm. These results highlight curcumin’s potential as a photoprotective agent, supporting safer, plant-based sunscreen formulations and offering a sustainable alternative for the cosmetic industry.